Linking Paleoclimate, Survey, and Farming Data at the Local Scale: A Case Study from Central Mesa Verde - S. Field; D. M. Glowacki (Journal of Computer Applications in Archaeology)
To understand human-climate dynamics in the past, archaeologists must reconstruct how social practices and climate conditions interacted at local scales. In this study, a stochastic approach that integrates regional paleoclimate models with survey and experimental farming data is used to refine maize farming estimates at Far View Community, a large, long-lived ancestral Pueblo community in present-day southwestern Colorado. Results from the model suggest that long-term maize success enabled the growth of the community between A.D. 700–980. However, persistent maize deficits from A.D. 980–1100, resulting from heightened demand and challenging climate conditions, undermined maize agriculture and ultimately contributed to the decline of the community. This study demonstrates the value of building models that localize the downstream subsistence consequences of climate stress, which can produce more nuanced understandings of how people and their communities were impacted by climate in the past.